2015
DOI: 10.1039/c5ra11489f
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of the in vitro toxicity of some functionalized carbon nanotubes and fullerenes

Abstract: Functionalized fullerenes and carbon nanotubes were investigated as regards in vitro cytotoxicity and hemolytic properties. Pristine carbon nanotubes (CNTs) were first shortened to make them compatible with cellular dimensions before functional groups were appended to their surface either covalently (e.g. amine, alcohol, carboxylate) or non-covalently (adsorption and polymerization of different polyethylene glycol-based amphiphiles). C60 fullerenes were covalently functionalized with polyethylene glycols of va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 58 publications
3
10
0
Order By: Relevance
“…Canapè et al have reported the hemocompatibility of the functionalized SWCNTs in human and rat RBCs. 47 Herein, the hemolytic activity of the developed nanoantibiotic was studied. Figure 5B shows the percentage of hemolysis at three concentrations (1, 10, and 20 µg/mL) after 2 and 24 h. It appears that there is no hemolytic activity of all tested concentrations for up to 24 h with a hemolysis percentage <10% as indicated in the literature.…”
mentioning
confidence: 99%
“…Canapè et al have reported the hemocompatibility of the functionalized SWCNTs in human and rat RBCs. 47 Herein, the hemolytic activity of the developed nanoantibiotic was studied. Figure 5B shows the percentage of hemolysis at three concentrations (1, 10, and 20 µg/mL) after 2 and 24 h. It appears that there is no hemolytic activity of all tested concentrations for up to 24 h with a hemolysis percentage <10% as indicated in the literature.…”
mentioning
confidence: 99%
“…Carbon nanotubes in their pristine form or with covalent (e.g., amine, alcohol, carboxylate) or non-covalent (e.g., PEG) surface modifications showed no hemolytic activity in the study of Canapè et al [171]. In vitro analyses showed that SWCNT, and in particular oxidized SWCNT, were not internalized by RBCs even at relatively high doses and did not induce hemolysis or toxic effects on human RBCs [172].…”
Section: Carbon Nanotubesmentioning
confidence: 93%
“…Consumption of C3 and C5 [154] No significant hemolytic activity [171] Pro-coagulant activity in a mouse model, formation of large intravascular aggregates [158]. Amplification of vascular thrombosis in rats (carotid artery) [160] C 2020, 6, 12 of 36 Minimal activation [158].…”
Section: Sw Cnts Pristinementioning
confidence: 99%
“…It was found that whereas one derivative had a negligible effect, the addition of an extra trifluoroacetate group induced a significant, time-dependent alteration of gene expression, mainly in biological processes involving protein synthesis, cell cycle progression and cell adhesion, with the authors suggesting an inhibition effect of the mTOR pathway. In a recent study performed by Canape et al, C 60 fullerenes were covalently functionalized with PEG of various sizes, Full-PEG2000, Full-PEG5000 and Full-PEG10000, and viability was studied on a variety of cell lines 24 h after exposure, evaluating mitochondrial activity, cell membrane integrity and hemolysis [48]. However, all the tested compounds were found to reduce, to some extent, the cellular metabolic activity, only two affected the cell membrane integrity, and none induced hemolysis.…”
Section: Fullerene C 60mentioning
confidence: 99%